2019
DOI: 10.5653/cerm.2019.00402
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 9 and cumulus cell supplementation in in vitro maturation culture media enhances the viability of human blastocysts

Abstract: Objective: In vitro maturation (IVM) of immature oocytes can be useful for some infertile patients. In IVM programs, the rates of embryo formation and pregnancy are low. Therefore, it is essential to recognize the main factors involved in regulating oocyte maturation in vitro. The purpose of this study was to investigate the effects of growth differentiation factor 9 (GDF9) and cumulus cell (CC) supplementation in IVM medium on the rates of embryo formation and viability of human blastocysts. Methods: A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…found that cumulus cell supplementation in IVM culture media enhances the viability of human embryos (blastocysts) after IVF. 40 The rates of in vitro matured oocytes in cancer patients and patients with fertility problems in our study were very similar to the published rates of IVM of immature oocytes in the usual IVF program, where 65.0%, 68.7%, 68.9% and 69.7% maturation rates were obtained in different maturation media. 41 , 42 , 43 Oktay et al .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…found that cumulus cell supplementation in IVM culture media enhances the viability of human embryos (blastocysts) after IVF. 40 The rates of in vitro matured oocytes in cancer patients and patients with fertility problems in our study were very similar to the published rates of IVM of immature oocytes in the usual IVF program, where 65.0%, 68.7%, 68.9% and 69.7% maturation rates were obtained in different maturation media. 41 , 42 , 43 Oktay et al .…”
Section: Discussionsupporting
confidence: 89%
“…26 Also Chatroudi et al found that cumulus cell supplementation in IVM culture media enhances the viability of human embryos (blastocysts) after IVF. 40 The rates of in vitro matured Non-significant differences, as revealed by Fisher's exact test oocytes in cancer patients and patients with fertility problems in our study were very similar to the published rates of IVM of immature oocytes in the usual IVF program, where 65.0%, 68.7%, 68.9% and 69.7% maturation rates were obtained in different maturation media. [41][42][43] Oktay et al reported the 45% increase in mature oocyte yield after IVM of immature oocytes after controlled hormonal stimulation of the ovaries in breast cancer patients and a high fertilization rate of these oocytes.…”
Section: Discussionsupporting
confidence: 86%
“…During the early development of IVM technology, fetal cord serum (FCS) [ 7 , 55 ], or human follicular fluid (HFF) [ 7 , 55 ], or human peritoneal fluid (HPF) [ 55 ] was added to human oocyte IVM medium. Later, patient’s own serum [ 48 ], or human serum albumin (HSA) [ 40 , 41 , 42 , 56 , 57 ], or synthetic substitutive serum (SSS) [ 9 , 39 ], or other synthetic serum substitutes [ 43 ] were used as a protein source supplement in the maturation medium. Considering the complex mixtures, batch-to-batch variability, and the potential risks of disease/infection transmission with protein supplements from biological sources, HSA and other synthetic serum substitutes are recommended for protein supplementations, as their compositions are relatively pure and well-defined.…”
Section: Culture Conditionsmentioning
confidence: 99%
“…The highest concentration at 0.75 IU/mL did not seem to play any role in enhancing IVM rates [ 20 , 29 , 62 , 63 , 64 ]. In most studies, FSH was usually used in combination with LH [ 43 , 56 , 65 , 66 ]/hCG [ 40 , 41 , 44 , 45 , 46 , 67 ].…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Some other factors also have been proved to promote oocyte maturation or benefit subsequent processes ( Table 3). The addition of GDF9 had no effect on maturation rate, while it significantly enhanced fertilization, embryo formation, and viability rates of blastocysts (82). And the growth hormone (GH) was applied to improve the IVM maturation rate of human oocytes (81).…”
Section: Maturation Stage: In Vitro Maturation (Ivm) Of Oocytesmentioning
confidence: 99%